Individualisation and the Practitionerʼs Paradox - Ivanovas, Georg (Homœopathic Links, 2012)
Most randomised trials on homeopathy are based either on a wrong epistemology, or on a misunderstanding of the homeopathic method, or on both. The result is logically irrelevant as seen with the efficacy paradox. In order to design trials appropriate to assess the effect of a homeopathic therapy, a more detailed understanding of the healing process is necessary. This article analyses some frequent mistakes of homeopathic trials.
Keywords: Randomised trials; Epistemology; Tuning; Practitionerʼs paradox